Mathematical Modeling Of Closed Loop Boost Converter (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Dc-Dc converters are electronic power circuits that convert a voltage of Dc to another voltage level of Dc. These circuits are often referred to as switching power supplies or switchers. The mathematical modeling of basic boost converter circuit is defined in this paper. High-quality, low or light weight, strong and effective control supplies are needed for cutting edge electronic frameworks. Linear power controllers working on the basis of a voltage or current divider are inefficient since they are limited to output voltages lower than the input voltage and also have a very low power density. In their active (linear) modes, linear regulators are bringing operated, but switching regulators are used at higher power levels. In turn-on and turn-off states, switching regulators use power-electronic semiconductor switches. There is a slight power loss in these states due to this, but switching regulators can achieve high efficiencies in energy conversion. It is possible to operate modern electronic power switches at high frequencies. The size of transformers, filter inductors and capacitors is reduced at the higher operating frequency, along with enhancements in the dynamic characteristics of converters with increasing operating frequencies. The closed loop converter has been designed for the stepping up from 12V to 30V with switching frequency of 25KHz.